Gorlin-Goltz syndrome: an uncommon case - Soni, Sonika; Mertia, Jolly; Mathur, Deepak; Jain, Disha (International Journal of Research in Dermatology, 2023)
Nevoid basal cell carcinoma syndrome, or basal cell nevus syndrome (Gorlin-Goltz syndrome), is a rare autosomal dominant inherited disorder which is characterized by multiple basal cell carcinomas from a young age. Other distinguishing clinical features that are seen in a majority of patients, includes keratocystic odontogenic tumors (formerly odontogenic keratocysts) and dyskeratotic palmar and plantar pitting. Estimated prevalence is 1 in 57,000 to 1 in 164,000. We report a case of this syndrome seen in a 43-year-old female patient with multiple black pigmented papules and plaques on face and trunk that first appeared when she was teenager. Her clinical features of were fitting within the criteria for the diagnosis of BCNS. Early diagnosis and treatment of this syndrome is important to reduce severity of complications including cutaneous and cerebral malignancy and oromaxillofacial deformation and destruction due to jaw cysts.